The Role of Work Engagement and Psychological Capital on Lecturers’ Readiness to Change in the Era of Technology-Based Education - Amalia, Rahmatika Sari; Fattah, Abdul; El Fahmi, Elok Fa’iz Fatma; halida, hilda (Gadjah Mada Journal of Psychology (GamaJoP), 2026)
Readiness to face technological developments refers to the readiness of lecturers to adapt to changes in the educationsector, which is increasingly using technology in every process. This readiness to change can be influenced by severalfactors, including work engagement and the psychological capital of the lecturers. This study aimed to explain the roleof work engagement and psychological capital on readiness to change using multiple linear regression analysis. Theparticipants in this study were lecturers from several public and private universities in Indonesia, grouped intoGenerations X and Y. Participants were recruited through convenience sampling, resulting in a total of 273participants. The results showed that work engagement and psychological capital simultaneously influence readiness tochange in Generation Y. Meanwhile, only work engagement can influence readiness to change in Generation X. The resultsof this study offer input for universities in Indonesia regarding recognizing the patterns of adjustment when it comesto each generation’s readiness to change in the face of challenges and demands to use the latest technologies ineducation.